Historiography after revisionism. Remarks on Pomian’s idea of writing history - Leszczyński , Marcin J. (Hybris, 2017)
Krzysztof Pomian’s works on history are one of the most interesting theoretical achievements of contemporary humanities. Being one of the prominent revisionists, Pomian took part in an important period of Polish history. Revisionist movement has also played an important role in shaping some basic ideas of Pomian’s later work. Article shows the meaning of revisionism in Polish tradition concerning historiography, and more specifically the meaning of Pomian’s ideas on historiography.